GENDER EQUALITY IN PERSPECTIVE CULTURE: A STUDY OF ROLES AND CHALLENGES FOR WOMEN IN ENDE REGENCY, EAST NUSA TENGGARA - Fatma Wati; Lely Suryani; Kristianus Jago Tute (SOSIOEDUKASI, 2025)
Gender equality is becoming an important issue in the development of social and economic conditions in Indonesia, including in Ende Regency, East Nusa Tenggara, which is still influenced by the culture of patriarchy. This culture places women in a subordinate position, limiting their access to education, employment, and public employment decisions. Thus, Ende women remain important players in family, economy, and social life. This research aims to analyze the role of women in social, economic, and cultural contexts, identifying obstacles faced, as well as explore strategies and policies to strengthen gender equality by paying attention to local wisdom. Research using a mixed-methods approach through questionnaires, in-depth interviews with women, character society, and gender activists, and field observations. Data analysis was carried out using a descriptive approach. phenomenology to understand the experience of women facing cultural patriarchy. The findings of this study show that local mark culture is strongly influential in the formation of the role of women, significant gender barriers still exist, and new government policy areas provide a partial contribution to social change. Therefore, the achievement of gender equality in Ende Regency requires synergy between public policy, community support, and women’s empowerment. This effort must be accompanied by the transformation of mark culture and the improvement of literacy, as well as the strengthening of women’s capacity to be able to participate actively in development. This finding confirms the need to approach structural and cultural aspects simultaneously to speed up the realization of sustainable gender equality in Ende Regency.